Queueing Systems with Resume Level - Bratiichuk, N. S.; Sliwinska, D. (Ukrains’kyi Matematychnyi Zhurnal, 2014)
A new approach is proposed for the investigation of the characteristics of queueing systems of the M/G/1/b-type with finite waiting rooms and a resume level of the input flow. A convenient algorithm is proposed for the numerical evaluation of stationary parameters of the system. Its efficiency is demonstrated for a specific system.